Self-Esteem and Academic Stress among Nursing Students - Acharya Pandey, R.; Chalise, H.N. (Kathmandu University Medical Journal, 2017)
Background Stress and self-esteem are common issues that everyone has to cope with at some time in their lives and they could also affect other things going on in a persons’ life. Academic stress is psychological condition often experienced by college students as, to some extent, being multidimensional variables. Among others are self-esteem and psychological well-being which are considered to have influences in explaining why college students experience stress. Objective The objective of this study was to assess the self-esteem level and academic stress among the nursing students. Method This is a cross-sectional study carried out in 2012. Total respondents were 190 nursing students selected randomly from Kathmandu University. Academic stress was assed using 30-item Scale for Assessing Academic Stress (SAAS) and Self esteem was assessed using 10 item Rosenberg’s Self-Esteem Scale. Information was collected through the self-administered questionnaire. The collected data was analyzed using SPSS version 16 software. Simple statistics measurement, percentage, means, correlation was used for the data analysis. Result This study shows mean age of the respondent’s was 20.44±2.67 years. Majority (88%) of students getting financial support of less than NRs 6000 per month and 64% have low perceived family support. This study found mean score of self esteem and academic stress was 11.9 and 18.4 respectively. Further nearly 78% students have low self esteem and 74% have high academic stress. Significant variable for high academic stress and low self esteem were lower the age, lower the education and low perceived family support. Lower financial support has also high academic stress. Conclusion Nursing students have low self esteem and high academic stress. Intervention to lower the academic stress and increase the self esteem should be carried out so that the learning of students will be efficient.